The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1108/ict-08-2018-0070
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the positive and negative affect schedule (PANAS) among employees in Indian manufacturing and service sector organisations

Abstract: Purpose The purpose of this paper is to examine the psychometric properties of the positive and negative affect schedule (PANAS) in a sample of employees working in Indian manufacturing and service sector organisations. Design/methodology/approach The data were collected through self-administered structured questionnaire from 53 employees for the pilot study and 383 employees for the final study. For the psychometric evaluation of the PANAS, item analysis, reliability, exploratory factor analysis, convergent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 28 publications
0
17
0
1
Order By: Relevance
“…In line with previous studies, discriminant validity (correlation with theoretically dissimilar construct) of SWLS was measured using two scales (Dahiya and Rangnekar, 2018b;Thompson et al, 2005). One being positive and negative affect schedule (PANAS; Dahiya and Rangnekar, 2019c) with two dimensions (positive affect [PA] and negative affect [NA]), containing ten items in each. The participants responded to a seven-point scale ranging from "never" as 1 to "always" as 7.…”
Section: Instrumentsmentioning
confidence: 95%
See 2 more Smart Citations
“…In line with previous studies, discriminant validity (correlation with theoretically dissimilar construct) of SWLS was measured using two scales (Dahiya and Rangnekar, 2018b;Thompson et al, 2005). One being positive and negative affect schedule (PANAS; Dahiya and Rangnekar, 2019c) with two dimensions (positive affect [PA] and negative affect [NA]), containing ten items in each. The participants responded to a seven-point scale ranging from "never" as 1 to "always" as 7.…”
Section: Instrumentsmentioning
confidence: 95%
“…Discriminant validity of the scale. Following the recommendation of Churchill and Iacobucci (2002), we examined the correlation coefficient between SWLS with two theoretical dissimilar scales, namely PANAS (Dahiya and Rangnekar, 2019c) and the HFS (Dahiya and Rangnekar, 2018b). The results of the coefficient of correlations showed that SWLS positively related with the positive affect (r 5 0.19, p < 0.01), negatively with negative affect (r 5 À0.14, p < 0.01) and positively related with forgiveness (r 5 0.18, p < 0.01).…”
Section: External Validity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In order to measure affect, participants were asked to respond to Positive and Negative Affect Schedule (PANAS) developed by Watson et al (1988) and validated in Indian manufacturing organizations by Dahiya and Rangnekar (2019b). The measure has two dimensions, namely positive affect and NA.…”
Section: Negative Affectmentioning
confidence: 99%
“…Similarly, two sample items for positive affect were: "I feel interested at work" and "I feel alert at work". Researchers have reported that both the dimensions of PANAS are related to each other (Dahiya & Rangnekar, 2019b;Watsson et al, 1988) and positive affect has a high likelihood of affecting this relationship (forgiveness and NA), hence, statistically controlled for analysis. A higher score means a higher level of NA in the respondents.…”
Section: Negative Affectmentioning
confidence: 99%